FIRE FIGHTING ROBOT - THOMAS, ANITHA; THELAPPILLY, JIMSON SHAJAN; P R, DHANYA; R, Deepa V; MG, Gireeshan (International Journal of Psychosocial Rehabilitation, 2020)
The motivation behind this project is that firefighter’s death. Many fire fighters are struggling to perform their duty which causes much death while on a mission and the circumstances to each incident. Firefighters are our heroes and our sense of security in times of trouble. They put themselves on dangerous situation to protect us. At present, the world is moving toward the use of technologies software and hardware. This paper proposed a smart firefighting robot system which designed to detect the source of fire, extinguish it and increase the knowledge about fire behaviour from incident area. This robot will reduce the risk of injury for firefighters and possible victims and decrease the monetary losses which increase considerably as fire duration increases. It consists of the ultrasonic sensor mounted on a servo motor for obstacles detection and equipped with flame sensors for detecting fire. It also makes use of liquid-tank and spray mechanism for extinguishing the fire. The spraying nozzle is mounted on a servo motor to cover maximum area. The whole system is programmed using an Arduino UNO board which forms the brain of the system. In addition to this the use of air sensors make it more applicable. It helps to detect the presence of toxic gases in the firing area.